Human pluripotent stem cell-derived cardiomyocytes: Genome-wide expression profiling of long-term in vitro maturation in comparison to human heart tissue - Piccini, Ilaria (Genom Data, 2015)
Cardiomyocyte-like cells (CMs) derived from human pluripotent stem cells (hPSCs) present a valuable model for human disease modeling, studying early human development and, potentially, developing cell therapeutic approaches. However, the specification of early hPSC-derived CMs into defined cardiac subtypes such as atrial and ventricular cells is not well understood and, thus, poorly controlled. Moreover, the maturation status of hPSC-CMs is not well defined, yet it is known that these cells undergo at least some degree of maturation upon longer term in vitro culture. To gain insight into this process, and to assess their developmental status, we have recently generated a data set of hPSC-CMs monitoring global changes in gene expression upon long term maintenance in vitro, in comparison to human atrial and ventricular heart samples (GEO accession number GEO: GSE64189). These data present a rich resource for evaluating the maturation status of hPSC-CMs, for identifying suitable markers for subtype-specific gene expression, as well as for the generation of functional hypotheses. Here, we provide additional details and quality checks of this data set, and exemplify how it can be used to identify maturation-associated as well as cardiac subtype-specific markers.